Rationing of Nursing Care and Professional Burnout Among Nurses Working in Cardiovascular Settings - Uchmanowicz, Izabella; Kubielas, Grzegorz; Serzysko, Bogusława; Kołcz, Anna; Gurowiec, Piotr; Kolarczyk, Ewelina (Frontiers in Psychology, 2021)
Introduction: Nursing needs close interpersonal contact with the patient and emotional involvement, therefore can contribute to professional burnout and rationing of nursing care. Aim: Assessing the relationship between the rationing of nursing care and professional burnout in nursing staff. Materials and Methods: The study included a group of 219 nurses working in cardiovascular facilities. This was a cross-sectional study designed to investigate the relationship between factors of the care rationing and professional burnout. The survey data was collected with standardised and research instruments such as the revised Basel Extent of Rationing of Nursing Care questionnaire (BERNCA-R) and the Maslach Burnout Inventory (MBI). Results: The total mean BERNCA-R score was 1.38 (SD = 0.62), while the total MBI score amounted to 38.14 (SD = 22.93). The specific components of professional burnout yielded the values: emotional exhaustion (M = 44.8), job dissatisfaction (M = 40.66), and depersonalisation (M = 28.95). Multiple linear regression showed that independent predictors of BERNCA-R score were emotional exhaustion, depersonalisation, job dissatisfaction, and multi-jobs activity (p < 0.001). Conclusion: The level of rationing of nursing care in cardiovascular facilities increases along with emotional exhaustion, depersonalisation and job dissatisfaction, and multi-jobs activity.